2018
DOI: 10.1002/cctc.201801306
|View full text |Cite
|
Sign up to set email alerts
|

The Metal Type Governs Photocatalytic Reactive Oxygen Species Formation by Semiconductor‐Metal Hybrid Nanoparticles

Abstract: Semiconductor‐metal hybrid nanoparticles (HNPs) are promising photocatalysts for redox reactions, including water reduction for hydrogen generation and reactive oxygen species (ROS) formation. Herein we study the effect of the metal co‐catalyst type on the light‐induced ROS formation using a combination of spectrophotometric and fluorescence assays, as well as electron paramagnetic resonance spectroscopy. We find that although Pt tips are more efficient for H2 generation, hydrogen peroxide and hydroxyl radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 44 publications
(84 reference statements)
2
30
0
Order By: Relevance
“…The Fermi level of the domain material alters the extent of fluorescence quenching, and consequently, the efficiency of the electronhole separation. Based on the relative alignment of the Fermi levels in the prepared hybrid nanostructures, [32,40,63] Pt and Au accumulate electrons more efficiently than in situ generated Co and Ni. This is in agreement with the measured QYs as well as average exciton lifetimes.…”
Section: Optical Properties and The Mechanism Behind Themmentioning
confidence: 99%
See 2 more Smart Citations
“…The Fermi level of the domain material alters the extent of fluorescence quenching, and consequently, the efficiency of the electronhole separation. Based on the relative alignment of the Fermi levels in the prepared hybrid nanostructures, [32,40,63] Pt and Au accumulate electrons more efficiently than in situ generated Co and Ni. This is in agreement with the measured QYs as well as average exciton lifetimes.…”
Section: Optical Properties and The Mechanism Behind Themmentioning
confidence: 99%
“…As a result, CdTe quantum dots (QDs), CdSe QDs, CdSe nanorods (NRs), CdS NRs and CdSe/CdS dot-in-rod NCs can be efficiently decorated with Ag, [18] Au, [19][20][21][22][23] Pt, [24][25][26] AuPd, [27] Ni, [28,29] Co [30][31][32][33] , Ni(OH) 2 , [34][35][36] or Co(OH) 2 [37] domains; furthermore, we also published a method for the site-selective growth of noble metals on CdSe/CdS core/crown NPLs. [38] The electronic structure of these hybrid NCs (i.e., band alignment, Fermi level) allows the enhancement of the light-induced charge carrier separation endowing them with high potential in photocatalytic applications such as water splitting [16,29,33,35,[37][38][39][40] or H 2 O 2 production. [40,41] Except solely few examples, the abovementioned synthetic procedures take place in organic solvents and require external trigger to initiate the reduction of the metal precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16a). 348 They have synthesized single-tipped CdS NRs (48 AE 5 nm  3.3 AE 0.5 nm) with either gold (2.5 AE 0.6 nm) or platinum (1.9 AE 0.5 nm) tips. Surprisingly they have found that though Pt is considered the 'better' H 2 (g) production catalyst, Au-tips have higher photocatalytic efficiencies towards H 2 O 2 and cOH generation.…”
Section: Nanoscale Advances Reviewmentioning
confidence: 99%
“…357 Many additional variations to the cadmium chalcogenide NR/M system were attempted to improve the stability and increase catalytic efficiencies-including variation of the NR's dimensions, CdSe@CdS seeded NRs, variation of tip size, number of metal catalysts, composition of the tip (core-shell, multi-domain, alloy bimetallic tips) and so forth. 100,348,351,[358][359][360] It is important to note that since the reaction conditions and measurement protocols are not standardized, it is hard to compare between different reports, especially since the illumination intensity and wavelength can change the number of photoexcited charge carriers per HNS and inuence the charge transfer mechanism. As pointed out by Ben-Shahar et al, this is especially important in photocatalytic reactions involving multielectron reactions such as water splitting.…”
Section: àmentioning
confidence: 99%